2016
DOI: 10.1159/000453367
|View full text |Cite
|
Sign up to set email alerts
|

Association between Obstructive Sleep Apnea and Acute Kidney Injury in Critically Ill Patients: A Propensity-Matched Study

Abstract: Background/Aims: Obstructive sleep apnea (OSA) is a known risk factor for chronic kidney disease (CKD); however, its association with acute kidney injury (AKI) is not well documented. We aimed to study whether OSA is associated with the risk of AKI in the intensive care unit (ICU) setting. Methods: All consecutive adult Olmsted County, MN residents who were admitted in Mayo Clinic ICUs from January 1, 2010 to December 31, 2010 were screened. Chronic and acute risk factors were collected within the first 48 h o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…In recent years, there have been several reports regarding novel and previously unknown risk factors for AKI, such as hyperuricemia 19 , hypoalbuminemia 20 , obesity 21 , obstructive sleep apnea 22 , hypochloremia and hyperchloremia 23 . In our study, BMI and obesity (COM2) were both selected in the top ten by several FS methods as shown in Table 4.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, there have been several reports regarding novel and previously unknown risk factors for AKI, such as hyperuricemia 19 , hypoalbuminemia 20 , obesity 21 , obstructive sleep apnea 22 , hypochloremia and hyperchloremia 23 . In our study, BMI and obesity (COM2) were both selected in the top ten by several FS methods as shown in Table 4.…”
Section: Resultsmentioning
confidence: 99%
“…It has been observed that patients with OSA are at a higher risk of acute kidney injury during critical illness. 21 In a longitudinal population-based cohort study, patients with OSA even without diabetes or hypertension are at higher risk of developing CKD over the next three years than the non-OSA cohort. 22 Hypoxia has been postulated to drive the pathogenesis of CKD, and this may be the dominant mechanism in such patients.…”
Section: Obstructive Sleep Apneamentioning
confidence: 99%
“…In patients without diabetes, OSA has been associated with CKD in cross-sectional and longitudinal studies. 2,53,84,85 Small studies of short duration suggested potential beneficial effects of CPAP on albuminuria and renal function. [86][87][88][89] In patients with T2D, a cross-sectional study of Japanese patients, Oxygen desaturation Index (ODI) ⩾5 was independently associated with microalbuminuria in women but not in men after adjustment for confounders.…”
Section: Osa and Diabetes Ckdmentioning
confidence: 99%